The Economic Effect of Tourist increase in MP: Analyzing the Impact of Tourism on the Economy of MP (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Economic growth is boosted by attracting more foreign direct investment (FDI) and building newinfrastructure as a result of increased tourism development. In recent years, there has been a great deal ofresearch on the contribution that tourism makes to economic development. Tourism has long beenrecognized as an important force for social progress and a method of fostering closer ties between peoplefrom different parts of the world, both economically and culturally. In recent years, several nations inboth the developing and industrialized world have turned to tourism as a long-term development option.At both the national and local levels, the impact of tourism may be seen. Nationally, tourism has asignificant roleadds to foreign currency profits and the balance of payments, while at the local level,tourism improves local lifestyles by creating jobs. It aids in the enhancement of living standards andinfrastructure. In this chapter, we will look at the influence of tourism not just on Mandla economy, butalso on its citizens.